2013
DOI: 10.1002/jmv.23523
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated clinical characteristics of hepatitis B, C, and HIV infections among injecting drug users in Korea

Abstract: Injecting drug use is associated with an increased risk of blood-borne viral infections, such as hepatitis B and C viruses (HBV and HCV, respectively) and human immunodeficiency virus (HIV). However, their prevalence, virological characteristics, and associated factors are not clear among the injecting drug users in Korea. The aim of this study was to determine the prevalence of HBV, HCV, and HIV infection, as well as their virological and clinical characteristics of injecting drug users in South Korea. Betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
3
21
1
Order By: Relevance
“…Nineteen studies reported the prevalence of HCV infection in high-risk populations: ten were from China [17][18][19][20][21][22][23][24][25][26], two from Japan [27,28], two from Korea [29,30] and five from Taiwan [12,[31][32][33][34]. Among high-risk populations, the prevalence of HCV infection was higher among IDUs (48-95 % in China, Table 4).…”
Section: Prevalence Of Hcv Infection In High-risk Populationsmentioning
confidence: 96%
“…Nineteen studies reported the prevalence of HCV infection in high-risk populations: ten were from China [17][18][19][20][21][22][23][24][25][26], two from Japan [27,28], two from Korea [29,30] and five from Taiwan [12,[31][32][33][34]. Among high-risk populations, the prevalence of HCV infection was higher among IDUs (48-95 % in China, Table 4).…”
Section: Prevalence Of Hcv Infection In High-risk Populationsmentioning
confidence: 96%
“…Among anti-HCV-positive persons, 98.1% were HCV RNA-positive 24. Meanwhile, in case of sharing cocaine suction pipe, the anti-HCV prevalence rate was similar to IVDU group 25…”
Section: Epidemiologymentioning
confidence: 78%
“…Domestic anti-HCV prevalence rate in the IVDU group was reported as 48.4-79.2% 21,22,23,24. Among anti-HCV-positive persons, 98.1% were HCV RNA-positive 24.…”
Section: Epidemiologymentioning
confidence: 95%
See 1 more Smart Citation
“…Although the screen for seropositivity of human immunodeficiency virus (HIV) infection was not performed because of legal and ethical issue, subjects who had positive results on hepatitis virus c (HCV) antibody and hepatitis virus b surface (HBs) antigen were excluded. The prevalence of HIV infection in South Korea is substantially low as compared with many other countries (Min et al, 2013; UNAIDS, 2012). Furthermore, the recent study examining 318 injecting drug users in South Korea has reported that HIV infections were not found while the prevalence of HCV and HBV infections was 48.4% and 6.6%, respectively (Min et al, 2013).…”
Section: Methodsmentioning
confidence: 99%